Review of Knowledge and Actions for Eradicating Dengue Fever Mosquito Nests - Saputri, Icha Maula; Widada, Agus; Gazali, Moh (Jurnal Sanitasi Profesional Indonesia, 2025)
Dengue fever is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. This disease is still a public health problem in Indonesia with a high mortality rate. Dengue fever occurs because it is related to environmental conditions accompanied by community knowledge and behavior, this study aims to determine the level of knowledge and action to eradicate dengue fever mosquito nests in the RT.16 community of Lingkar Timur Village, Bengkulu City. The design of this study is descriptive, the population of this study is all people domiciled in RT.16 Kelurahan Lingkar Timur as many as 40 people, data was collected through a questionnaire with 20 multiple-choice questions regarding respondents' knowledge of the causes, symptoms, and prevention of dengue fever, and an observation sheet with questions containing 15 questions regarding the eradication of dengue fever mosquito nests. The results of this study indicate that 23 people (57.5%) of the community have a poor understanding of eradicating dengue fever mosquito nests and 36 people (90.0%) have a poor category regarding the action of eradicating dengue fever mosquito nests. The results of this study can be used as a reference and information to increase insight into mosquito nest eradication for the wider community.